The Relationship between Maternal Knowledge Level and Early Diarrhea Treatment in Toddlers in the Working Area of the North City Health Center - Afifah Nazirah Ramdhani; Nurdiana Djamaluddin; Rini Wahyuni Mohamad (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Diarrhea is one of the main causes of pain and death in toddlers, especially due to complications such as dehydration. Prompt and appropriate initial treatment is necessary to prevent more serious impacts. The role of mothers as the main caregiver is very important in determining the actions taken when toddlers experience diarrhea. One of the factors that affect these actions is the mother's level of knowledge. This study aims to determine the relationship between the level of knowledge of mothers and the initial treatment of diarrhea in toddlers in the work area of the North City Health Center. This study uses an analytical observational design with a cross-sectional approach. A total of 34 samples were taken using the total sampling technique. The research instruments are in the form of a Questionnaire on the Level of Knowledge of Mothers and a Questionnaire on Early Treatment of Diarrhea in Toddlers which have been tested for validity and reliability. The results showed that the level of knowledge of mothers was in the sufficient category as many as 15 respondents (44.1%) and the initial treatment of diarrhea was in the good category as many as 29 respondents (85.3%). The results of the Chi-Square test showed a significant relationship between the mother's level of knowledge and the initial treatment of diarrhea in toddlers (p < 0.05). This study shows that the better the mother's level of knowledge, the more appropriate the action taken. Meanwhile, there are still a small number of mothers with less knowledge and less action, so continuous education improvement is needed.